CFD simulation and parametric study of Rijke Tube - Wong, Zhi Yao (Nanyang Technological University, 2020)
For the thermo-acoustic instabilities to be sustained in a Rijke Tube, the Rayleigh criterion has to be satisfied. However, there are many factors that can affect the acoustic pressure and temperature, resulting in a lack of reliable methods to predict the occurrence of thermal instabilities in combustion chambers. In this report, a simulation is developed to investigate and analyse the thermo-acoustic instabilities in a Rijke Tube. The study is done to better understand the pressure and velocity fluctuations of a Rijke Tube and how different parameters in the simulation can affect the simulation outcome of the Rijke Tube. Ansys Fluent was used for this project to simulate the thermo-acoustic instability found in the Rijke Tube. Different turbulence models were tested for accuracy in simulating the conditions in a Rijke tube. Additionally, multiple parameters such as the boundary conditions of the farfield, material and boundary conditions of the tube, temperature of the heat source and the solving approach were varied. The outcomes of the simulations with different parameters were then compared and analysed.